(untitled) (Journal of the College of Education for Women, 2019)
Abstract :Algeria had lacked the appropriate size of forces that achieved to it themilitary balance to face the foreign threats or to achieve its security.Consequently , this demanded Algeria to put a complete plan to reach theappropriate size by forces . These Forces needed to be built according to thefollowing standards :– The national gool for Algeria and how to achieve it through the armed forces.- Specifying the size of threats with a kind of detail , the size of these threatswould be specified in the future in order to build its Force according to FutureFrames and limits .- Developing the abilities of war manufacturing .- Specifying the necessary Funds in the Future budgets that would provide theFinancial suppart to build the necessary military abilities .- Developing the armed Forces according to the modern systems and to be upwith the international developments in this Field .- Cooperating with the countries of Arab Maghrib to gain experiences throughjoint manoeuvres , along with efforts to unity the systems of arming andtraining in order to Facilitate the ,military co – operation .- Building a unified strategy within the Arab Maghrib countries , this requiresAlgeria to constitute a military leadership and to build appropriate joint Forcesthat would achieve the military policy in the Future .